PROBLEM-BASED LEARNING, STRATEGI METAKOGNISI, DAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA - Sastrawati, Eka -; Rusdi, Muhammad -; -, Syamsurizal - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The present study investigates effect of Problem-Based Learning (PBL) model and metacognition strategies on higher-order thinking skill of students in Mathematics Lesson. The independent variables are PBL design instructional and the expository and discussion learning design. The moderator variable is metacognition strategies measured by the adaptation OLRc News 2004. Questionnaires and structured-essay tests are used as research instruments. The dependent variable is higher-order thinking skills of Secondary school students. The experiment uses 2 x 2 factorial design with pretest and posttest. The samples are splitted into two groups: the PBL group and the conventional group of 32 students of each group. The study reveals that there are (1) the influence of the PBL model on higher-order thinking skills, (2) the influence of metacognition strategies on higher-order thinking skills, (3) the influence of PBL model on higher-order thinking skills of a group of students with high metacognition strategies, (5) there is an interaction between the PBL models and metacognition strategies against students’ high-level thinking skills. Keywords: problem based learning, metacognition strategy, higher-order thinking skills